2013
DOI: 10.1056/nejmc1302511
|View full text |Cite
|
Sign up to set email alerts
|

Proteotoxicity and Cardiac Dysfunction

Abstract: Baseline physiological function of the mammalian heart is under the constant threat of environmental or intrinsic pathological insults. Cardiomyocyte proteins are thus subject to unremitting pressure to function optimally and this depends upon them assuming and maintaining proper conformation. This review explores the multiple defenses a cell may employ for its proteins to assume and maintain correct protein folding and conformation. There are multiple quality control mechanisms to ensure that nascent polypept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 175 publications
0
11
0
Order By: Relevance
“…77 Amyloidosis represent the deposition of insoluble, fibrillar proteins in a cross b-sheet structure that characteristically binds dyes such as Congo red. The most common form of age-related or senile amyloidosis is limited to the atrium, a condition known as isolated atrial amyloidosis (IAA).…”
Section: Pathology Of Atrial Cardiomyopathiesmentioning
confidence: 99%
“…77 Amyloidosis represent the deposition of insoluble, fibrillar proteins in a cross b-sheet structure that characteristically binds dyes such as Congo red. The most common form of age-related or senile amyloidosis is limited to the atrium, a condition known as isolated atrial amyloidosis (IAA).…”
Section: Pathology Of Atrial Cardiomyopathiesmentioning
confidence: 99%
“…As a post-mitotic cell, cardiomyocytes possess little, if any, replicative capacity in adult life (Bergmann et al, 2009). Thus, maintaining balanced protein quality is fundamental to minimize cellular dysfunction and death (Willis and Patterson, 2013). At the same time, it has been firmly established that metabolic derangements contribute to the pathogenesis of heart disease (Lopaschuk et al, 2010).…”
Section: Protein Quality Control In Heart Diseasementioning
confidence: 99%
“…Studies in the preclinical setting have shown that the HSPs have a cardioprotective role against cellular stress. Sensing of cellular stress leads to activation of heat shock transcription factor-1 (HSF-1) which upregulates the expression of HSPs [5]. HSP-60 plays an important role in cytoprotection by preventing denaturation and enhancing proper assembly of cellular proteins [23].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological risk factors for AF such as aging, valvular heart disease, hypertension and cardiomyopathy cause atrial stretch and adverse remodeling, which mediate the pathogenesis of AF [3]. Preclinical studies have demonstrated that induction of heat shock proteins (HSPs) has a cytoprotective role against various cardiac diseases [4, 5]. HSPs play an important role in protein-protein interactions such as the establishment of proper protein confirmation and prevention of unwanted aggregation that occurs during cardiac stress [5, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation